PENGARUH TRANSFER PRICING, PERENCANAAN PAJAK, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MULTINASIONAL SUBSEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022 – 2024: PENGARUH TRANSFER PRICING, PERENCANAAN PAJAK, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MULTINASIONAL SUBSEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022 – 2024 - Stefhani Stevi Yoma Onayangga; Diana Airawaty (JURNAL ILMIAH EDUNOMIKA, 2025)
This study was conducted to determine the effect of transfer pricing, tax planning, and capital intensity on tax avoidance in multinational mining companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The population and sample were determined using purposive sampling. The data analysis technique used SPSS. Based on the data output, the research results show that transfer pricing has a significant effect on tax avoidance in multinational mining companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Tax planning does not have a significant effect on tax avoidance in multinational mining companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Furthermore, capital intensity has a significant effect on tax avoidance in multinational mining companies listed on the Indonesia Stock Exchange for the 2022-2024 period.